Clarithromycin Resistance in Helicobacter Pylori - Bolor-Erdene, Mandkhai; Namdag, Bira; Jav, Sarantuya (Central Asian Journal of Medical Sciences, 2016)
Objectives: Eradication rates of Helicobacter pylori with standard triple therapy are disappointing in studies from several countries. The main reason for failure was found to be bacterial resistance to one of the most commonly used antibiotics, clarithromycin. Our aim was to determine the prevalence of clarithromycin resistance among H. pylori strains isolated from Mongolians and the presence of associated mutations to these antibiotics. Methods: All urease-positive samples were cultured according to the standard microbiological procedures. H. pylori strains were grown under microaerophilic conditions on H. pyloriselective agar. H. pylori antibiotic sensitivity was examined using the E-test method. The GenoType HelicoDR, which employs reverse hybridization, was used to confirm the presence of H. pylori, determine its susceptibility to antimicrobials and detect mutations conferring resistance to clarithromycin. Results: Ourfindings show that 51 (53.7%) ofH. pyloristrains were resistantto clarithromycin. Mutations were observed in 32 (53.7%) strains with A2147G being the most prevalent, A2146G being the least prevalent and A2146C point mutation being undetected. Conclusion: In the present study, H. pylori strains with moderate-level clarithromycin resistance are more frequently found and clarithromycin is associated with point mutation A2147G in Mongolians.